Model Ibadah Sekolah Minggu Kreatif-Interaktif bagi Generasi Alfa di Gereja Toraja - Daniel Fajar Panuntun; Rinaldus Tanduklangi; Merry Adeng; Christian Eleyazar Randalele (Institut Agama Kristen Negeri Toraja, 2019)
: Industrial revolution 4.0 is bringing great impact into the global world, including children from the alpha generation. The alpha generation have a typical characteristic that need to gain a concern in terms of spiritual needs. Sunday schol expecially Toraja’s Church need to do an inovation to fulfill the spiritual need of The alpha generation. This study use Research and Development (RnD) method. The research produce a product which is a book with the tittle Sekolah Minggu Kreatif-Inovatif.The book is produced by a kualitatif approach with interactive analysis. The development of the product is done by critism of participant about the product. The result is a Sekolah Minggu Kreatif-Inovatif book For the alfa generation of Toraja’s Church with the collaborative and confrontative principle.Abstrak: Revolusi Industri 4.0 menghasilkan pengaruh besar bagi dunia global, salah satunya pada anak-anak generasi alfa.Anak-anak generasi alfa memiliki ciri khas yang perlu untuk mendapatkan perhatian dalam hal kebutuhan rohaninya. Sekolah Minggu terkhusus di Gereja Toraja perlu untuk melakukan inovasi untuk menjawab kebutuhan rohani anak-anak generasi alfa. Kajian ini menggunakan jenis penelitian dan pengembangan (RnD). Penelitian menghasilkan produk buku Sekolah Minggu Kreatif-Inovatif yang dihasilkan melalui pendekatan kualitatif dengan anali-sis interaktif. Pengembangan produk dilakukan dengan kristisi partisipan mengenai hasil produk yang dihasilkan.Hasil Akhir adalah buku Sekolah Minggu Kreatif-Inovatif bagi Generasi Alfa Gereja Toraja berdasarkan prinsip kolaboratif dan konfrontatif.